Development of agent based model for simulating of building consultants teamwork - Zaharaddeen Salihu, Kado (2014)
Agent Based Model (ABS) is a recently intoduced System Simulation Model (SSM) which mainly emphasized on agent variables and their relationships between the communications of one or more agents known as “agent parameters”. It is possible that one simply can’t see that there is a sequential process of information simulation, but one may have a clear view on how the agent parameters in the system model behave individually. Nowadays, the organizations and industries were increasingly relying on team working, to stream their day to day operations, processes, enhance participation, and improve performance. Teamwork is of worldwide importance, the individuals who wish to participate fully in community and professional life must increasingly possess the skills necessary to work in a team. Building industry is a massy enterprise were business processes of project management were taking place in a teamwork, which is been handled by the group known as “Building Consultants Team”. The information simulation and communication within and out the consultant’s team members was massy and its really of importance to be addressed, due to it insufficient, inadequate and lack of good communication in their teamwork environment. The aim of this research project case study is to develop an Agent Based Model (ABS) for simulation of Building Consultants Teamwork (BCT). Therefore, the model was designed with partial embedded some part of Enterprise Ontology (EO) concept of modeling approach, which mainly emphasized on the agent parameters and their communications relationships. The Agent Based Model (ABS) was been analyzed and validated by the experts’ in this field (i.e the BCT members), and their feedback were through the interview questionnaires. The results shows that all the experts approved the ABS Model, and the agent parameters and their communication relationships in addressing the information simulation in the Building Consultants’ Teamwork (BCT)